AAUW leader works to support opportunities for women. Issue 7 (19th September 2022) - Santovec, Mary Lou
Abstract : The travel bug hit Gloria Blackwell in middle school. Having taken her first French class and discovering she was really good at languages, she soon found herself part of a group of students involved with a sister city exchange in France.